2008
DOI: 10.1007/s10886-008-9520-5
|View full text |Cite
|
Sign up to set email alerts
|

EAG-Active Herbivore-Induced Plant Volatiles Modify Behavioral Responses and Host Attack by An Egg Parasitoid

Abstract: Volatiles emitted by plants in response to feeding by Lygus species were tested in neurophysiological, behavioral, and parasitism trials with Anaphes iole, an egg parasitoid of Lygus. Electroantennogram analyses indicated that A. iole antennae responded to most herbivore-induced plant volatiles (HIPVs) tested and that females were usually more responsive than males. Antennal responses to (Z)-3-hexenyl acetate and methyl salicylate were among the strongest. Behavioral assays in a four-arm olfactometer demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 56 publications
1
32
0
Order By: Relevance
“…Induced plant volatiles are also exploited by mymarids [43,44] (Table 1). Feeding on cotton, and several other plants, by either sex of Lygus hesperus Knight (Miridae) results in the induction of volatiles that are behaviorally and physiologically active towards Anaphes iole Girault (Mymaridae).…”
Section: Exploitation Of Indirect Versus Direct Host-related Chemicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Induced plant volatiles are also exploited by mymarids [43,44] (Table 1). Feeding on cotton, and several other plants, by either sex of Lygus hesperus Knight (Miridae) results in the induction of volatiles that are behaviorally and physiologically active towards Anaphes iole Girault (Mymaridae).…”
Section: Exploitation Of Indirect Versus Direct Host-related Chemicalmentioning
confidence: 99%
“…Therefore, egg parasitoids have developed specialized strategies to overcome the reliability-detectability dilemma in order to efficiently parasitize host eggs. Successful parasitism is accomplished hexenyl acetate, methyl salicylate Attraction in olfactometer (effect of experience); response to EAG [43,44,67] Short range synomones…”
Section: Introductionmentioning
confidence: 99%
“…Ample evidence exists in the literature from laboratory studies that natural enemies can respond to HIPVs (Mumm & Dicke, 2010). For example, Anaphes iole Girault, an egg parasitoid of Lygus spp., showed a strong antennal response (based on electroantennogram -EAG-analysis) to (Z)-3-hexenyl acetate and MeSA (Williams et al, 2008). Gas chromatographic-electroantennographic detection (GC-EAD) analysis showed that MeSA elicits a significant antennal response in C. septempunctata (Zhu & Park, 2005).…”
Section: Mechanism Of Attractionmentioning
confidence: 99%
“…For example, four HIPVs: linalool, (E)--ocimene, (3E)-4,8-dimethyl-1,3,7-nonatriene, and MeSA attracted females of the predatory mite P. persimilis in Y-tube olfactometer assays (Dicke et al, 1990b;De Boer & Dicke, 2004a). In a wind tunnel, Williams et al (2008) showed attraction of A. iole females to MeSA and -farnesene. Thus, it is safe to infer that natural enemies are also being directly attracted to the synthetic lure in the field.…”
Section: Mechanism Of Attractionmentioning
confidence: 99%
See 1 more Smart Citation